أثر الإتصالات التسويقية الرقمية على ولاء الزبائن للعلامة التجارية – دراسة حالة علامة صومام: The impact of Digital Marketing Communications on Consumers Brand Loyality Case study of SOUMMAM brand - نجيمي عيسى; كويحل مراد (Journal of North African Economies, 2025)
This study aims to test the nature of the impact of digital marketing communications whith its dimensions: online marketing- social media marketing- mobile marketing- electronic word of mouth on consumers brand loyality, a case study of SOUMMAM brand. A questionnaire was designed and distributed randomly through the distribution of an electronic one targeting 384 consumers, the statistical package for the social sciences SPSS have also been used to analyze and test the study hypotheses. The results of the study concluded that the digital marketing communications had a positive impact on consumers loyality of SOUMMAM’s brand, and also there are positive impact of:online marketing- social media marketing- word of mouth, and there was no impact of mobile marketing.